2013
DOI: 10.1055/s-0033-1343952
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Outcomes and Flap Selection in Free Tissue Transfers for Complex Lower Extremity Reconstruction

Abstract: Patient comorbidities and defect location can be associated with higher rates of complications; flap selection and delayed venous thrombotic events appear to be associated with flap failure.Level of Evidence Prognostic/risk category, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…This analysis revealed that the gracilis flap was the 3 rd most utilized flap after the anterolateral thigh flap and latissimus dorsi flap 14 . Our failure rate is consistent with this and other published reports 12,14,18 . In a retrospective review of 119 free flaps in 114 patients, Fischer et al reported using the gracilis free flap in only 3 (2.5%) cases.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This analysis revealed that the gracilis flap was the 3 rd most utilized flap after the anterolateral thigh flap and latissimus dorsi flap 14 . Our failure rate is consistent with this and other published reports 12,14,18 . In a retrospective review of 119 free flaps in 114 patients, Fischer et al reported using the gracilis free flap in only 3 (2.5%) cases.…”
Section: Discussionsupporting
confidence: 94%
“…Our flap loss rate of 8% is in line with published reports of free flap survival in lower extremity reconstruction 12,18,19,23 . It is important to acknowledge that while we lost only 2 flaps completely, our 1 partial flap loss led to exposure of critical structures despite the majority of the flap surviving.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations